(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, global trends in beauty, cosmetic, and personal care products are developing at a faster rate. For this reason, numerous businesses engaged in e-commerce to sell their products. Supposedly, a lot of beauty and personal care products are increasing based on consumer demand. Fake cosmetic and personal care items are among the concerns and problems that Esta’s Bella Boutique has encountered. They were able to distinguish fake products from real ones by their physical differences. Thus, the owner only avails of stocks from trusted suppliers. This study aims to determine customers’ level of satisfaction with Esta’s Bella Boutique in terms of price, brand, and quality. The results of this study reveal the customers’ level of satisfaction with Esta’s Bella Boutique; the satisfaction was evaluated as "very highly satisfied" in terms of price, brand, and quality. The problems encountered by the two groups concerning the product and the solutions made by the owner in terms of "the products contain too many harmful ingredients which damage the skin" and there is a crafted proposed guideline to enhance the level of satisfaction of the customer. This study recommended that the business should consistently maintain the products it offers to sustain customer satisfaction. Also, continue to implement affordable products from reputed brands with quality and legal safety to prevent issues about products that contain too many harmful ingredients that damage the skin. The researchers proposed guidelines that will enhance the level of satisfaction of the customers. Keywords: Business Administration